An Interactive Web-Based Circuit Design and Analysis Interface for Disabled Students by Using Speech Recognition Technology - (:unkn) unknown (IEEE, 2017)
This paper presents a web-based interface for disabled students. When the curriculum of engineering faculties are examined, it can be seen that practice takes important place and learning outcomes of the courses is mostly depend on hand ability. In particular, the implementing and testing the electronic circuits in both real and simulated environments requires using hands. The developed hands-free interface enables the students to design DC circuits including adjustable batteries and resistors. Students can design the circuits, run the simulation and observe the results by speaking. Thus, the huge gap between the disabled students and circuit design can be closed. The circuit diagrams are designed in accordance with the mesh current method and user can design multi-loop circuits. The interface uses Web Speech API (WSA) speech recognition technology to transform the speech into text. Chrome is the only browser that can support WSA. Adobe Flash was used to visualize the circuit and Symbolic Circuit Analysis in MatLab (SCAM) program was used for circuit analysis and calculations.
Keywords: Speech Recognition; Web Speech API; Circuit Design and Analysis; Disabled Individuals; SYSTEM